The Artificial Intelligence on trial: a vision of its conquest of the world and the danger rooted in legal development - Jara Zavaleta, Jhabel Jordano (2024)
When we imagined the future world as children, it was inevitable to escape from the contemplation of machines that performed human tasks, arduously programmed to be of service to man. Today we do not need to approach distant realities to get closer to that idealization, because the modern world has laid the foundations of a civilization increasingly dependent on technology. Tools such as artificial intelligence have appeared on the global market in recent years and it is estimated that they are getting closer and closer to the fields of knowledge in which human aptitude performs. The main purpose of this paper is to reflect on the conditioning factors that prevail in the use of artificial intelligence applied to law and to know to what extent this may be detrimental to the legal system itself, which responds to a series of characteristics linked to human reasoning.